Unraveling the Burden of Iron in Neurodegeneration: Intersections with Amyloid Beta Peptide Pathology - Uranga, Romina Maria (2018)
Iron overload is a hallmark of many neurodegenerative processes such as Alzheimer's, Parkinson's, and Huntington's diseases. Unbound iron accumulated as a consequence of brain aging is highly reactive with water and oxygen and produces reactive oxygen species (ROS) or free radicals. ROS are toxic compounds able to damage cell membranes, DNA, and mitochondria. Which are the mechanisms involved in neuronal iron homeostasis and in neuronal response to iron-induced oxidative stress constitutes a cutting-edge topic in metalloneurobiology. Increasing our knowledge about the underlying mechanisms that operate in iron accumulation and their consequences would shed light on the comprehension of the molecular events that participate in the pathophysiology of the abovementioned neurodegenerative diseases. In this review, current evidences about iron accumulation in the brain, the signaling mechanisms triggered by metal overload, as well as the interaction between amyloid β (Aβ) and iron, will be summarized.